2018
DOI: 10.1242/jeb.174474
|View full text |Cite
|
Sign up to set email alerts
|

Are the surface areas of the gills and body involved with changing metabolic scaling with temperature?

Abstract: The metabolic-level boundaries (MLB) hypothesis proposes that metabolic level mediates the relative influence of surface area (SA)- versus volume-related metabolic processes on the body-mass scaling of metabolic rate in organisms. The variation in the scaling of SA may affect how metabolic level affects the metabolic scaling exponent. This study aimed to determine the influence of increasing metabolic level at a higher temperature on the metabolic scaling exponent of the goldfish and determine the link between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…Q 10 of SMR in fish is typically between 1.62 and 2.40 (Clarke & Johnston, 1999;Killen et al, 2016), with which the Q 10 of P. fluviatilis' SMR found in the present study (1.91) matches well. Although it is shown in previous studies (Ohlberger et al, 2012;Li et al, 2018), we found no interaction between temperature and body mass on SMR indicating no change in the mass scaling coefficient of SMR with temperature change in P. fluviatilis.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Q 10 of SMR in fish is typically between 1.62 and 2.40 (Clarke & Johnston, 1999;Killen et al, 2016), with which the Q 10 of P. fluviatilis' SMR found in the present study (1.91) matches well. Although it is shown in previous studies (Ohlberger et al, 2012;Li et al, 2018), we found no interaction between temperature and body mass on SMR indicating no change in the mass scaling coefficient of SMR with temperature change in P. fluviatilis.…”
Section: Discussioncontrasting
confidence: 92%
“…This variation can to a large extent be ascribed to ontogeny (Killen et al ., 2007) and the ecological lifestyle of a species (Killen et al ., 2016). Furthermore, temperature may also affect mass scaling exponents of ṀO 2 (Li et al ., 2018; Ohlberger et al ., 2012; Tirsgaard et al ., 2015), which was one of the main focusses of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the underlying mechanisms of metabolic scaling remain unclear. Recently, a growing number of studies have implied that, in addition to the SA and metabolic level of whole organisms, SA at the organ level and the cellular level and their scaling may contribute to the allometric scaling of MR (Okie 2013;Hirst 2014;Luo et al 2015Luo et al , 2020Gillooly et al 2016;Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the changes in the exponent b of the RMR (b R ) with temperature vary among species. In most cases, b R is reduced by increasing temperature (Xie and Sun 1990;Ohlberger et al 2007Ohlberger et al , 2008Ohlberger et al , 2012Killen et al 2010;Li et al 2018), which can be explained according to the metabolic level boundaries hypothesis (Glazier 2005(Glazier , 2008(Glazier , 2009(Glazier , 2010(Glazier , 2014. At high temperatures, high metabolic demand results in metabolic scaling being primarily determined by fluxes across surfaces (scaling as M 2/3 ).…”
Section: Introductionmentioning
confidence: 99%